An exploration of street robberies at Bungeni Village under Makhado Municipality, Limpopo Province, South Africa - Hlungwani, Hlamalani Mildred (My University, 2021)
The purpose of this study was to explore street robberies at Bungeni village, situated under Makhado Municipality of Limpopo Province, South Africa. The study sought to identify factors contributing to street robberies, to assess experiences of victims of these robberies and to determine measures that can be applied to prevent them. This qualitative study applied the exploratory research design to recruit participants using non-probability sampling techniques, specifically purposive and snowball sampling techniques. Thirteen (13) participants, including ten (10) victims of street robbery and three (3) local SAPS officials were selected for this study. Data was collected using individual face-to-face semi-structured interviews. Based on the transcribed data, themes were extracted and analysed using Thematic Content Analysis (TCA). This study established that there are factors that contribute to the occurrence of street robberies; victims are affected by street robberies (i.e. be it social, psychological and financial); and that there are measures that may reduce the occurrence of these robberies. Findings of the research indicate that factors such as time, space, individual’s lifestyle and routine activities contribute to victims being robbed in the streets and that these victims experience victimisation of street robberies differently. For recommendations, this study argues that some of these factors are lifestyle exposure, individual activities, spatial and temporal factors. Street robberies are characterised by the use of weapons, force and threat of force by offenders. Lastly, street robberies have a negative impact on victims. Keywords: Aggravated robbery, Crime prevention, Robbery, Street robbery and Victims
Thesis(M.A. (Criminology)) -- University of Limpopo, 2021
Keywords: Aggravated robbery; Crime prevention; Robbery; Street robbery; Victims; Robbery; Criminals -- South Africa -- Limpopo; Crime prevention -- South Africa -- Limpopo; Victims of crimes -- South Africa -- Limpopo